2000
DOI: 10.1088/0022-3727/34/1/101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of a dielectric barrier discharge lamp using short-pulsed excitation

Abstract: We observe marked increases in the time-averaged intensity, peak intensity, efficiency and spectral purity of the VUV output from an Xe excimer barrier discharge lamp when using short-pulse (~150 ns FWHM (full width half maximum)) excitation. Intensity increases with Xe pressure up to 600 Torr with a maximum output 2.6 times higher and an efficiency 3.2 times higher than the same lamp excited by conventional ac excitation (i.e. sinusoidal voltage waveform). The output occurs in regular short pulses (<300 ns FW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 5 publications
10
98
0
2
Order By: Relevance
“…Rare gas DBDs can be used for excilamps Boyd I W 2000, Boichenko A M et al 2004], mercury-free lamps [Jinno et al 2005], for oxidation of silicon at 250 °C [Kogelschatz U et al 2000]. Operating in xenon or neon, they produce VUV or EUV (10 nm < λ < 100 nm) emissions with an efficiency as high as 50 to 60% [Vollkommer F and Hitzschke L 1996, Hitzschke L and Vollkommer F 2001, Mildren R P and Carman R J 2001, Carman R J and Mildren R P 2003, Carman R J et al 2004, Merbahi N et al 2007, Carman R J et al 2010. In order to understand their behaviour, stable MF-DBDs were must be achieved at frequencies around tens of kilohertz [Adler F and Muller S 2000, Sewraj N et al 2009, Merbahi N et al 2004, Merbahi N et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Rare gas DBDs can be used for excilamps Boyd I W 2000, Boichenko A M et al 2004], mercury-free lamps [Jinno et al 2005], for oxidation of silicon at 250 °C [Kogelschatz U et al 2000]. Operating in xenon or neon, they produce VUV or EUV (10 nm < λ < 100 nm) emissions with an efficiency as high as 50 to 60% [Vollkommer F and Hitzschke L 1996, Hitzschke L and Vollkommer F 2001, Mildren R P and Carman R J 2001, Carman R J and Mildren R P 2003, Carman R J et al 2004, Merbahi N et al 2007, Carman R J et al 2010. In order to understand their behaviour, stable MF-DBDs were must be achieved at frequencies around tens of kilohertz [Adler F and Muller S 2000, Sewraj N et al 2009, Merbahi N et al 2004, Merbahi N et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the impact of the power supply on the plasma can modify the processes which occur, for example, in dielectric barrier discharge lamps [16][17][18] or ozone generator [19][20][21]. In [16], Mildren showed that the efficiency and light intensity (between 175 and 200 nm) are improved when the lamps are supplied by a pulsed power supply (rather than an AC power supply), and photographs of the light emission are presented in [17]. When using an ozone generator, Williamson obtained the same results [19], with the pulsed power supply producing more ozone than an AC power supply.…”
mentioning
confidence: 99%
“…We see that the density of the metastable state decreases with the increasing of the gas pressure. This diminution in metastable density is due in part to its conversion to Xe 2 * ( 3 Σ u + ), collision with the fundamental state of xenon [21,22,60]. However, we can expect that the reaction R3 (see Table 1) can also contribute to this diminution as the pressure increasing induces a decrease in the plasma electric field.…”
Section: Effect Of Pressurementioning
confidence: 99%